ÙÙ‡Ù… Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ù‡Ø¯Ø§ÙŠØ© Ø§Ù„Ù‚Ù…Ø±ÙŠØ© Ø¹Ù† Ø§Ù„ØªÙˆØÙŠØ¯ ÙÙŠ ÙƒØªØ§Ø¨ Ø¹Ù‚ÙŠØ¯Ø© Ø§Ù„Ø¹ÙˆØ§Ù… - Muhammad Hidayaturrahman (UIN Fatmawati Sukarno Bengkulu, 2023)
This study was conducted to determine the understanding of Hidayatul Qomariyah Islamic boarding school students of the values of tawhid in the book of Aqidatul Awam. The problem formulations in this study are: 1.How do the students understand the values of tawhid in the 10 obligatory attributes of Allah? 2.What are the factors that influence the understanding of the book of Aqidatul Awam?The type of research used in this study is descriptive qualitative. Data collection techniques used in this study using observation, interviews and documentation. Data validity techniques using triangulation techniques. The data analysis technique uses the interactive model of miles and huberman. The subjects in this study were 10 students of the 1st grade tsanawiyah Islamic boarding school Hidayatul Qomariyah and 3 ustadzah who taught the Aqidatul Awam book.Based on the results of the study, it shows that the students' understanding of the values of tawhid in the book of Aqidatul Awam is said that the 1st grade tsanawiyah students have understood the values of tawhid well. This is seen by many respondents who have given the correct answer and refer to the theory.